Anti-inflammatory mechanisms of fruits and by-products from Mauritia flexuosa, an exotic plant with functional benefits#. Issue 11 (3rd June 2021) - Amorim, Vivianne Rodrigues; Rodrigues, Débora Caroline do Nascimento; Silva, Jurandy do Nascimento; Ramos, Carla Lorena Silva; Almeida, Lívia Maria Nunes; Almeida, Antonia Amanda Cardoso; Pinheiro-Neto, Flaviano Ribeiro; Almeida, Fernanda Regina Castro; Rizzo, Marcia Santos; Pereira-Freire, Joilane Alves; Ferreira, Paulo Michel Pinheiro
ABSTRACT: Mauritia flexuosa L., traditionally known as "buriti", exhibits chemoprotective properties including antioxidant, antithrombotic, and nutritional actions. The aim of this study was to examine the oral anti-inflammatory activity of epicarp, mesocarp and endocarp obtained from M. flexuosa fruits using in vivo models to verify physiological benefits. The anti-edematogenic action was determined using phlogistic agents to induce paw edema and peritonitis. Pro-inflammatory cytokines, cell migration of peritoneal cells, histological changes, and abdominal swelling induced by acetic acid were also investigated. Carrageenan-induced edema was found to be decreased in mice pre-treated with epicarp by 50.8%, 53.7% and 39.2% and mesocarp by 41.8%, 65.3% and 71.9% after 2, 3, and 4 hr stimuli, respectively. Edema initiated by specific agents such as compound 48/80, histamine, serotonin, and prostaglandin E2 were also reduced, and better outcomes were found against histamine-induced edema, as evidenced by the decline at all times analyzed (30–120 min) with both doses of water extract of mesocarp (500 or 1000 mg/kg). Mesocarp-pre-treatment reduced inflammatory tissue parameters such as number of peritoneal leukocytes and TNF-α levels, but only epicarp diminished abdominal pain. In summary, M. flexuosa fruits, especially mesocarp, exhibited oral physiological benefits and capacity to modify biochemical and cellular steps in the inflammatory cascade, indicating that dietary supplements containing these fruits may be combined with pharmacological tools to ameliorate or prevent diseases of inflammatory origin.